Perancangan Media Promosi Sebagai Upaya Pengenalan Toko Kopi Sido Mukti Malang - Jonathan Jonathan; Sultan Arif Rahmadianto; Ayyub Anshari Sukmaraga (Citradirga : Jurnal Desain Komunikasi Visual dan Intermedia, 2022)
Industry 4.0 is marked with the increasing of information tecnology uses. This store which has been around since 1950 hasn’t been using information technology for its promotion. This final project has the purpose to design a promotion media with Insagram and printed media to promote Sido Mukti Coffeeshop so that it can compete in the industry era 4.0. Qualitative method is used to describe an object. Design technique is started with data collection through observation, interviews, and documentation. From the observation, the data obtained is about the situation of the store and its surounding. From the interviews, the data obtain is about the history of the store, the store development, photos, and videos. The theme of the design that is used is vintage with cross-hatching illustration. The final output is instagram design and other supporting printed media. The conclusion is, its better if all kind of business is up to date with the developments that exist so that they can compete without leaving any advantages that is offered. It is hoped that the next designer is able to explore Sido Mukti Coffeeshop’s advantages that hasn’t been showed yet.